2019
DOI: 10.1177/1369433219879805
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the seismic performance of composite columns with an ultra-high-strength concrete-filled steel tube core

Abstract: The ultra-high-strength concrete-encased concrete-filled steel tube column consists of a concrete-filled steel tube core and a rectangle-shaped reinforced concrete encasement. This article presents the seismic performance analysis of ultra-high-strength concrete-encased concrete-filled steel tube columns subjected to cyclic loading. Based on the measured load-lateral displacement hysteresis curves of six ultra-high-strength concrete-encased concrete-filled steel tube columns and two conventional RC columns, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In 2018, Yang Yiting et al [9] conducted a simulation analysis of the mechanical properties of 7 steelconcrete columns under low-cycle repeated loads. The results showed that high-strength steel-concrete columns with large shear-to-span ratios, low axial compression ratios, high hoop reinforcement ratios, and high steel content tend to exhibit fuller hysteresis loops, indicating stronger ultimate deformation capacity of the specimens.…”
Section: High Seismic and Impact Resistancementioning
confidence: 99%
“…In 2018, Yang Yiting et al [9] conducted a simulation analysis of the mechanical properties of 7 steelconcrete columns under low-cycle repeated loads. The results showed that high-strength steel-concrete columns with large shear-to-span ratios, low axial compression ratios, high hoop reinforcement ratios, and high steel content tend to exhibit fuller hysteresis loops, indicating stronger ultimate deformation capacity of the specimens.…”
Section: High Seismic and Impact Resistancementioning
confidence: 99%
“…To improve the mechanical performance of the outer concrete, Xu et al [25] and Dai et al [26] proposed the use of outsourcing angle steel to strengthen the concrete outside the steel tube. Yang et al [27] suggested using the prestressed steel strips to strengthen the restraint of the concrete outside the steel tube. While these methods can enhance the mechanical properties of CFCST columns, they also present certain challenges, including complexity and high costs.…”
Section: Introductionmentioning
confidence: 99%